BREAKING BARRIERS: FEMALE DIRECTORS, EARNINGS MANAGEMENT, AND THE INFLUENCE OF EDUCATION AND SUSTAINABILITY REPORTING - Ramadana, Mariska; Pratama, Vincent Tio; Butar-Butar, Dea Tiara Monalisa (Universitas Bunda Mulia, 2024)
Background: The role of women directors in corporate governance has received increasing attention, especially regarding their impact on earnings management. Recognizing this role is critical as companies need to increase transparency and accountability in their financial practices, while recognizing the role of sustainability.Objective: These studies aim to find out, whether female participation in the board of directors can reduce earnings management practices, by adopting different types of measurements for the female variable.Research Method: The applied methods are purposive sampling where 49 samples collected from Indonesia Stock Exchange (IDX) that consistently publishing financial and sustainability report with a timeframe of 2018-2022. Implementing data panel regression method using Stata application.Result: The result indicate that, three female director can reduce earnings management, while independent commissioner and GRI disclosure are positively related to earnings management.Originality/Novelty of Research: This studies use different kind of measurements towards female director variables, to proving applied theory are still relevant and to resolve the limitation of previous studies to find the critical effect of female directors participation to decreasing earnings management in Indonesia.